2017
DOI: 10.4067/s0718-95162017000300001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exogenous 24-Epibrassinolide in Enhancing the Salt Tolerance of Wheat Seedlings

Abstract: To understand the functions of exogenous 24-Epibrassinolide (EBR) in enhancing the salt tolerance of wheat (T. aestivum L.) seedlings to salt stress, a hydroponic experiment was performed to investigate the effects of EBR on chlorophylls, root activity, H + -ATPase, malondialdehyde (MDA), electrolyte leakage, free proline, soluble protein, reactive oxygen species (ROS), antioxidant enzymes and minerals content in wheat plants subjected to non-stress conditions or salt stress (120 mM NaCl) with foliar applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 30 publications
(59 reference statements)
6
31
0
Order By: Relevance
“…The present study demonstrated that salinity stress can significantly reduce the chlorophyll content of apple seedlings, and exogenous BL treatment can recover the content to normal levels (Figure 2A). The recovery of chlorophyll contents after the exogenous application of BL might be due to the modulation of transcription and translation processes by BR signaling, which ultimately stimulates chlorophyll biosynthesis and inhibits the breakdown of chlorophyll molecules (Sharma et al, 2016;Dong et al, 2017). Moreover, the present study indicated that the photosynthetic rate of the apple seedlings was reduced by salt stress, and exogenous BL application significantly improved photosynthetic rate under salt stress ( Figure 2B).…”
Section: Discussionmentioning
confidence: 52%
“…The present study demonstrated that salinity stress can significantly reduce the chlorophyll content of apple seedlings, and exogenous BL treatment can recover the content to normal levels (Figure 2A). The recovery of chlorophyll contents after the exogenous application of BL might be due to the modulation of transcription and translation processes by BR signaling, which ultimately stimulates chlorophyll biosynthesis and inhibits the breakdown of chlorophyll molecules (Sharma et al, 2016;Dong et al, 2017). Moreover, the present study indicated that the photosynthetic rate of the apple seedlings was reduced by salt stress, and exogenous BL application significantly improved photosynthetic rate under salt stress ( Figure 2B).…”
Section: Discussionmentioning
confidence: 52%
“…18 ℃ 8 h darkness, 65% relative humidity (Dong et al 2017). Seven days after sowing, plants at the same growth stage were selected and transplanted to containers filled with Hoagland solution.…”
Section: Methodsmentioning
confidence: 99%
“…For relative water content was calculated ( Fig. S3) as follow: RWC(%) = (FW - DW)/FW × 100 (Dong et al 2017). The chlorophyll content (Song et al 2016) was determined ( Fig.…”
Section: Measurement Of Biomass and Physiological Index In Wheat Seedmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in osmotic stress and cell structure are induced by Ca(NO 3 ) 2 . Therefore, it leads to increased cellular levels of Ca 2+ and NO 3 − that inhibit plant growth nutritional absorption, especially moisture and ion absorption [3]. Ca 2+ is the second messenger in the plant.…”
Section: Introductionmentioning
confidence: 99%